Optimization of supercritical nuclear power system based on sodium cooled fast reactor. Issue 2 (February 2019) - Zhao, Zhenxing; Liao, Mengran; Wei, Wei; Wu, Jun; Wang, Wei
Abstract: By modeling the supercritical carbon dioxide Brayton recompression cycle on sodium-cooled fast reactor, the effects of parameters on cycle characters were studied. The high-efficiency and wide-range Brayton cycle was optimized. The results show that the assumptions of constant temperature or constant power cannot reflect the real efficiency variation of S-CO2 Brayton cycle. The supercritical cycle and the transcritical cycle have different requirements for operating parameters. The downward turning point of the turbine output power corresponds to the peak of cycle efficiency for S-CO2 Br ayton cycle. The different split rates are corresponding to different optimal mass flow rates.